If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+3(2x-6)=6
We move all terms to the left:
2x+3(2x-6)-(6)=0
We multiply parentheses
2x+6x-18-6=0
We add all the numbers together, and all the variables
8x-24=0
We move all terms containing x to the left, all other terms to the right
8x=24
x=24/8
x=3
| –3p–10=5 | | x÷6+x+2=x+11-5(4-x) | | 17+20+13w=20w−12 | | 172=58-y | | q2+1=50 | | –18d+8=–17d | | 2x+5=3x× | | n-18=-13 | | x+0.15x=7068 | | 9x+22=33x | | x+0.15x=240 | | M^3-4m-9=0 | | Z^3-4z-9=0 | | 88/4x+12=36/2x | | 5x+7=9x+2 | | 25x+x=100–50= | | 3x^+7x+16=16 | | (3x-1)×4=74 | | x=6x+3=5x−8 | | X+6x+3=5x−8 | | 5y+34=7y+42 | | X7-2=5x+10 | | 4(x+4)=-2x-14 | | 2x-6+9x=5 | | 9m−3m−2=0 | | 9m2−3m−2=0 | | X^3=6x^ | | -b/5-37=-21 | | (4v-2)=(2v-4) | | 7w+50=30+5w | | -s+7=6 | | 17x=18-(4x.25) |